2014
DOI: 10.1128/aem.02717-13
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Bioactive and Probiotic Marine Bacteria and Their Secondary Metabolites in Artemia sp. and Caenorhabditis elegans as Eukaryotic Model Organisms

Abstract: bWe have previously reported that some strains belonging to the marine Actinobacteria class, the Pseudoalteromonas genus, the Roseobacter clade, and the Photobacteriaceae and Vibrionaceae families produce both antibacterial and antivirulence compounds, and these organisms are interesting from an applied point of view as fish probiotics or as a source of pharmaceutical compounds. The application of either organisms or compounds requires that they do not cause any side effects, such as toxicity in eukaryotic org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…TDA is a broad-spectrum antibacterial that is bactericidal and inhibits the growth of several human and fish pathogens (16,(21)(22)(23) but has very low toxicity in Caenorhabditis elegans and Artemia (24). Recently, it was demonstrated that TDA is cytotoxic against N2a cells and OLN-93 cells of the mammalian nervous system and several cancer cell lines, respectively (25,26).…”
mentioning
confidence: 99%
“…TDA is a broad-spectrum antibacterial that is bactericidal and inhibits the growth of several human and fish pathogens (16,(21)(22)(23) but has very low toxicity in Caenorhabditis elegans and Artemia (24). Recently, it was demonstrated that TDA is cytotoxic against N2a cells and OLN-93 cells of the mammalian nervous system and several cancer cell lines, respectively (25,26).…”
mentioning
confidence: 99%
“…In a recently discovered alternate route, the prolyl alpha-carboxyl carbon atom is lost during the biosynthesis of 1 and the cytotoxic marine bacterial natural product pentabromopseudilin (5, Fig. 1) (4,11). Uniquely, 5 is biosynthesized via the coupling of 2,3,4-tribromopyrrole (6, Fig.…”
mentioning
confidence: 99%
“…natural products | biosynthesis | halogenation | enzymology M arine bacteria of the genus Pseudoalteromonas produce numerous small molecule natural products with varied roles in marine chemical ecology (1)(2)(3)(4). Recently, tetrabromopyrrole (1, Fig.…”
mentioning
confidence: 99%
“…While the participation of flavoenzymes as halogenating catalysts in chlorinated natural product biosynthesis is well established (Figure 2AB) [24], it is surprising to note that physiological marine brominating flavoenzymes, those that cannot catalyze the oxidative incorporation of chlorine [25], had evaded discovery until very recently. Querying the genetic and molecular bases for the biosynthesis of the cytotoxic [26] marine natural product pentabromopseudilin revealed the ‘ bmp ’ gene locus that incorporates two intriguing flavin-dependent brominases [27]. Of these, the enzyme Bmp2 catalyzes the tribromination of L-proline derived pyrrole ring that is acylated to an acyl carrier protein (ACP) (Figure 2C).…”
Section: Bromination In the Biosynthesis Of Toxic Polybromophenols Anmentioning
confidence: 99%